PENGARUH PENGGUNAAN MEDIA VIDEO BERBASIS KEARIFAN LOKAL TERHADAP HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR - Aprilia Elsa Faridha; Eka Fitriana HS; Siti Nurul Haliza; Satriawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the use of video media based on local wisdom on the mathematics learning outcomes of elementary school students. This research is an experimental research using a quantitative approach. This research took place at UPT SPF SD Inpres Perumnas antang III. The population of this study is students who are randomly selected in classes IVA, IVB, and IVC by sampling, namely using simple random sampling. The sample in this study was 28 students in class IVC consisting of 14 males and 14 females. The research instruments used were observation sheets, learning outcome tests and documentation. Data analysis uses descriptive statistical analysis and inferential statistical analysis. Descriptive statistical analysis where the teacher's activity obtained an average score of 3.5 with the very good category, then the results of the analysis of student activities obtained an average score of 3.5 with the very good category. The average score of pretest student learning outcomes was 9.61, and posttest 80.00. Furthermore, the inferential statistical analysis in this study shows that the results of the prerequisite test consist of pretest normality test 0.128 and posttest 0.158, homogeneity test results 0.369 and hypothesis test 0.044. So that H₁ is accepted, H₀ is rejected. Based on the results of the analysis, it can be concluded that the use of video media based on local wisdom has an effect on students' mathematics learning outcomes.